Field guide to the arrhythmias - Lader, Ellis W. (Chichester ; Hoboken : John Wiley & Sons, 2013)
Field Guide to the Arrhythmias adopts the familiar time-tested format of the naturalist's field guide - the handy little books which, for example, hikers might use to identify woodland flora and fauna - to teach one of the most vexing subjects of clinical medicine: arrhythmia identification. The book's humorous approach, which is based in sound pedagogy and supported by considerable research into the effectiveness of employing humor to help learners master complex and difficult subjects. This book is very much in keeping with the playful spirit of the "Dummies" books Wiley publishes.
Preface -- Acknowledgments -- Abbreviations -- Part 1. The rhythms. Normal sinus rhythm ; Preexcitation ; Sinus bradycardia ; Sinus tachycardia ; Sinus arrhythmia ; Wandering atrial pacemaker ; Multifocal atrial tachycardia ; Junctional rhythm ; Asystole ; Heart block: first degree, second degree (Mobitz I and II), and third degree (complete) ; Premature beats (blocked and otherwise) ; Atrial fibrillation ; Atrial flutter ; Supraventricular (paroxysmal atrial) tachycardia ; Pacemaker rhythms ; Ventricular tachycardia ; Accelerated idioventricular rhythm ; Prolonged QT/Torsades de pointes ; Ventricular fibrillation -- Part 2. Multiple choice questions.
Includes bibliographical references and index.
Print version record.
Keywords: Arrhythmia; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Arrhythmia; Electronic books